Assessment of employee satisfaction of training & development: a study on employee of Prime Bank Limited - Parveen, Rumana (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.